The determinants of inflation rate in Malaysia / Solehah Mohamad - Mohamad, Solehah (Faculty of Business and Management, 2015)
The main purpose of this research is to examine the determinant factors of inflation in Malaysia. The relationship between macroeconomic factors namely money supply, unemployment rate, exchange rate, gross domestic product and oil price with inflation are studied. This research study covers quarterly data for the time period for the period of first quarter 2007 to fourth quarter 2014. The time series data for the entire dependent and independent variables are to be non-stationary at the level but stationary at first difference. The results show both long-run and short-run relationships between money supply, unemployment rate, exchange rate, gross domestic product and oil price with inflation.